PENGEMBANGAN JARINGAN JALAN DIKAWASAN PERBATASAN BERDASARKAN ASPEK KEWILAYAHAN(STUDI KASUS KECAMATAN PALOH DAN KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS) - -, Yoelyanto (Jurnal Teknik Sipil, 2019)
The change of the border paradigm to the front porch of the Republic of Indonesia, has changed the development on the border of Sambas District in the District of Paloh and District Sajingan Besar. The amount of central budget to accelerate the development of the border is accompanied by the rapid growth of public housing and the increase of community activities. The position of the road network as part of the transportation system that connects and binds all the activities center needs to be prepared its road space, in anticipation of social problems in the future. The method of regional analysis with the 'strategic choice' approach used is' Analysis of Interconnected Decision Areas (AIDA), as the daily traffic volume in the two sub-districts is still low. The decision areas are the areas of the villages located in the sub-district and so do the related areas, where these decision areas are linked to the affecting aspects of regional planning. The results of the analysis show that arterial roads are located in that areas, while the arterial road width in District Paloh and District Sajingan Besar sub-district is still eligible and Right of way (ROW) for the future is expected of 45 m. Road collectors at this border are still eligible and must be prepared ROW up to 14 m. As for local roads should be prepared ROW up to 7.5 m.